Application of graphene oxide based Microfiber-Knot resonator for relative humidity sensing - Azzuhri, Saaidal Razalli; Amiri, Iraj Sadegh; Zulkhairi, Aiman Syahirah; Salim, Muhammad Aizi Mat; Razak, Mohd Zulhakimi Ab; Khyasudeen, Muhammad Farris; Ahmad, Harith; Zakaria, Rozalina; Yupapin, Preecha Promphan (Elsevier, 2018)
A relative humidity (RH) sensor is proposed and demonstrated using a micro-knot resonator (MKR) enhanced with a layer graphene oxide (GO) coating. The MKR is fabricated by means of tapering a standard fiber, with the GO coating added by the drop-cast method. The proposed sensor is tested for an RH range of between 0% and 80% at 20% intervals, and the configurations with and without the GO coating achieve sensitivities of 0.0104 nm/% and 0.0095 nm/%, respectively. The MKR configuration without the GO coating has a linear response correlation coefficient of 0.9098 and a resolution of 0.1%, while the configuration with the GO coating has a linear response correlation coefficient of 0.9548 and a resolution of 0.096% which is better. The proposed sensor has multiple applications, especially in the area of climate and atmospheric measurement and monitoring.